Is Political Science (Still) Ignoring Religion? An Analysis of Journal Publications, 2011–2020 - Kettell, Steven (PS, political science & politics, 2024)
Political scientists involved in the study of religion have expressed concerns that religious themes have yet to be fully integrated into the mainstream of the discipline. According to a study of articles published in leading political science journals during the first decade of the twenty-first century, papers engaging with religion were relatively few in number and highly concentrated in only a few thematic and disciplinary areas. This article presents an updated analysis of the extent to which political science has engaged with the topic of religion by examining journal outputs for the period 2011–2020. The study finds no significant change in the patterns identified by the earlier research. Despite an overall increase in the quantity of political science articles on the subject of religion, the overall proportion has been relatively static, and the thematic and disciplinary focus of outputs remains narrow.